Sex Is as Sex Does : Governing Transgender Identity - Currah, Paisley, 1964- (Book collections on Project MUSE., 2022)
"In this book, the author shows that the misclassification of transgender people, a phenomenon usually thought to be the result of transphobia, was in the past often deeply connected to systems that ensure the legal oppression of women. With the gradual disestablishment of gender from the state, barriers to sex reclassification began to crumble and contradictions in sex reclassification policies emerged-one state actor determining that sex classification is inalterably determined at birth, another demanding gender confirming surgery, a third requiring only an avowal of gender identity. While trans advocates attempt to rectify the injustice by talking about what sex and gender really are, the author demonstrates that policymakers have often been more concerned with what sex does for a particular state project. Sometimes it has been a tool for nation-building, as in marriage law; sometimes it has been a tool for affirming identity or tracking individuals, as in identity documents. Setting aside debates about "the correct" definitions of sex and gender, he examines how sex has been put to work as a mobile technology of governing. The book also illustrates how, in the current climate, sex reclassification has been weaponized by the right"--